2017
DOI: 10.1021/acs.langmuir.7b01699
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Fluorescent Boron Nitride Quantum Dots via a Hydrothermal Strategy Using Melamine as Nitrogen Source for the Detection of Ferric Ions

Abstract: A facile and effective approach for the preparation of functionalized born nitride quantum dots (BNQDs) with blue fluorescence was explored by the hydrothermal treatment of the mixture of boric acid and melamine at 200 °C for 15 h. The as-prepared BNQDs were characterized by transmission electron microscopy (TEM), high-resolution TEM, atomic force microscopy, X-ray photoelectron spectroscopy, UV-vis spectroscopy, and fluorescence spectroscopy. The single layered BNQDs with the average size of 3 nm showed a blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 36 publications
8
99
0
Order By: Relevance
“…The control experiment confirmed the fluorescence of the stained silk fiber was not from the scattering light . These results showed that the MQDs could be potentially used as fluorescent imaging and staining reagent for further chem‐ or bioimaging …”
Section: Resultsmentioning
confidence: 55%
“…The control experiment confirmed the fluorescence of the stained silk fiber was not from the scattering light . These results showed that the MQDs could be potentially used as fluorescent imaging and staining reagent for further chem‐ or bioimaging …”
Section: Resultsmentioning
confidence: 55%
“…AFM images (Figure e‐h) further confirm the uniformity of the as‐synthesized BNQDs. The AFM height profiles (inset of Figure e‐h) demonstrate typical topographic height of the BNQDs ranging from 0.76 to 1.93 nm, corresponding to 1–3 BN layers …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, its further application is seriously limited. Recently, Huo et al . proposed a economical and promising approach for the preparation of functionalized BNQDs by the hydrothermal treatment of the mixture of boric acid and melamine at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…30 This is in agreement with previous literature reports. 18,25 As illustrated in the inset of Fig. 2a, the dark dot shows clear lattice fringes of 0.34 nm, corresponding to an interplanar d(002)-spacing.…”
mentioning
confidence: 95%
“…36 The presence of carbon in BN QDs is common and has been reported. 18,35,37 Compared to hydro-/solvothermal routes, bottom-up pyrolytic syntheses of BN, more so under the presence of ammonia 38 , aid the removal of carbon from the end product. 27,28 To gain further insight into the relative atomic surface composition and chemical states of the elements, we collected high resolution core level B 1s, C 1s, N 1s and O 1s spectra through XPS.…”
mentioning
confidence: 99%